HELMINTHFAUNA OF MAGELLANIC PENGUIN (SPHENISCUS MAGELLANICUS FOSTER, 1781) PROCEEDING FROM ILHA COMPRIDA, SOUTH COAST, STATE OF SÃO PAULO, BRAZIL - Barbosa de Medeiros do Prado, Maria Izabel (2011)
The present study aims to identify the helminth fauna of Spheniscus magellanicus Foster, 1781 from themunicipality of Ilha Comprida, southern São Paulo State. A total of 28 individuals were analyzed,resulting in an identification of three helminth species: Contracaecum pelagicum Johnston &Mawson, 1942, Cardiocephaloides physalis Sudarikov, 1959 and Tetrabotrium lutzi Parona, 1901.Contracaecum pelagicum and C. physalis were core species, while T. lutzi was considered a satellitespecies. All individuals examined were infected with at least one species (overall prevalence = 100%).The host specimens were all juveniles and the infection may be associated with food items eaten duringmigration to the Brazilian Coast.